Time at or near VO2max during continuous and intermittent running: A review with special reference to considerations for the optimisation of training protocols to elicit the longest time at or near VO2max - Midgley, A. W.; McNaughton, L. R. (The Journal of Sports Medicine and Physical Fitness, 2006)
Several authors have suggested that training at or near VO2max (i.e. >=95% VO2max) is the most effective training intensity to enhance VO2max and that for highly trained endurance athletes, training at or near VO2max may be necessary to increase it further. Consequently, there is an interest in characterising training protocols that allow the longest time at or near VO2max (T@VO2max). Intermittent running protocols have been found to be more effective than continuous protocols for increasing T@VO2max. Intermittent protocols can be manipulated by altering the warm-up intensity and timing, work and relief interval velocity and duration, amplitude, interval number per set, and the number of sets performed. To increase T@VO2max it is recommended that work interval intensity should generally range between 90% and 105% vVO2max and relief interval intensity between 50% vV.O2max and the lactate threshold velocity. Work and relief interval durations should be between 15 and 30 seconds. The warm-up period prior to the intermittent protocol should be about 10 to 15 minutes in duration at 1 or 2 km·h-1 below the lactate threshold velocity, with no gap between the warm-up and the intermittent protocol. When designing intermittent training protocols for the enhancement of VO2max, the simultaneous enhancement of other physiological performance determinants should also be considered. Further experimental research is required to identify the specific physiological responses and adaptations to various intermittent running protocols that are designed to elicit the longest time at or near V.O2max, before recommendations can be given to competitive endurance runners.